2005
DOI: 10.3727/096504005776449716
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Stem Cell Differentiation Stage Factors of Intermediate-Advanced Hepatocellular Carcinoma: An Open Randomized Clinical Trial

Abstract: There is no standard treatment for patients with advanced hepatocellular carcinoma (HCC). We developed a product containing stem cells differentiation stage factors (SCDSF) that inhibits tumor growth in vivo and in vitro. The aim of this open randomized study was to assess its efficacy in patients with HCC not suitable for resection, transplantation, ablation therapy, or arterial chemoembolization. A total of 179 consecutive patients were enrolled. We randomly assigned the patients to receive either SCDSF or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…We may assume that in cancer stem cells the trajectory of multifaceted cross-talk between the genetic/epigenetic environment and cell signaling networks may undergo a deviation from the road map for terminal differentiation. Such hypothesis is supported by decisive experiments performed by Biava and Coworkers [1,[25][26][27][28][29] showing that factors extracted from zebrafish embryos at different stages of embryonic development (embryonic stagedependent factors) are able to induce differentiation and/or apoptosis of human cancer stem cells, bypassing the mutations that are at the origin of the malignant tumor.…”
Section: Cancer Stem Cell Reprogrammingmentioning
confidence: 91%
See 1 more Smart Citation
“…We may assume that in cancer stem cells the trajectory of multifaceted cross-talk between the genetic/epigenetic environment and cell signaling networks may undergo a deviation from the road map for terminal differentiation. Such hypothesis is supported by decisive experiments performed by Biava and Coworkers [1,[25][26][27][28][29] showing that factors extracted from zebrafish embryos at different stages of embryonic development (embryonic stagedependent factors) are able to induce differentiation and/or apoptosis of human cancer stem cells, bypassing the mutations that are at the origin of the malignant tumor.…”
Section: Cancer Stem Cell Reprogrammingmentioning
confidence: 91%
“…In this regard, it has been shown that the proliferation curves of human tumor cell lines can be slowed down following the exposure to extracts of zebrafish embryos collected during the phases of cell differentiation. On the contrary, there is no significant anti-proliferative effect in the presence of extracts solely yielded from the initial duplicative phase of zebrafish embryogenesis [25][26][27][28][29]. itself ) with consistent sequelae of intracellular events [33,35].…”
Section: Tuning Human Cancer Stem Cell Dynamics With Chemical Agents:mentioning
confidence: 99%
“…5 The stem cells seem to create signals leading to the inhibition of cell proliferation and stimulation of differentiation. 6 Tumor cells are capable of secreting factors that can attract hMSCs to the tumor site. 7 MSCs were proven to regenerate damaged livers.…”
Section: Introductionmentioning
confidence: 99%
“…Kubota et al (13) reported that bone marrow cells (BMCs) fused with some oval cells but that the BMC-fused oval cells and BMCs did not have malignant potential in rats fed with the cholinedeficient, ethionine-supplemented diet. Another study suggested that the stem cell microenvironment may play an essential role in preventing carcinogenesis by providing signals to inhibit proliferation and to promote differentiation (14). Moreover, evidence is emerging that supports the premise that stem cells may serve as a vehicle for the transfer of genetic material in the treatment of patients with HCC, especially for those not suitable for resection, transplantation, ablation therapy, or arterial chemoembolization (15).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence is emerging that supports the premise that stem cells may serve as a vehicle for the transfer of genetic material in the treatment of patients with HCC, especially for those not suitable for resection, transplantation, ablation therapy, or arterial chemoembolization (15). In a clinical trial, treatment with stem cell differentiation stage factors showed inhibition of tumor growth in patients with HCC (14), but the underlying mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%